Virulence factors of Candida species from the oral mucosa and prostheses of elderly people from a riverside community in the Amazon state, Brazil - Daniela Marinho da SILVA; Thayana Cruz de SOUZA; Carol Falcão de Carvalho ALENCAR; Ingrid da Silva de SOUZA; Maria Fulgência Costa Lima BANDEIRA; Ormezinda Celeste Cristo FERNANDES (Universidade Estadual Paulista, 2019)
Abstract Introduction Candida albicans is the yeast most commonly affecting the oral cavity, sometimes causing infection. However, several factors may be associated with the onset of candidiasis, which may be related not only to the hygiene and health of individuals, but also to the pathogenicity of these microorganisms. Objective To evaluate the virulence factors of Candida yeasts isolated from the oral mucosa of elderly people living in the "Comunidade Lago do Limão", municipality of Iranduba, Amazonas state, Brazil. Material and method Testes were performed to assess the production of urease, proteinase, phospholipase and hemolysin. Statistical analysis used the Fisher's exact test and the Chi-squared test. Result Prevalence of non-albicans species was observed. As for virulence factors, all isolates were negative ureases, and there was prevalence of very strong proteinase production, whereas most isolates did not produce this enzyme in the phospholipase test. All yeasts analyzed presented hemolysin production, with grade IV hemolysis as the most prevalent. There was no statistically significant difference between the virulence of isolates from the oral cavity and the prostheses of the elderly analyzed. Conclusion Several virulence factors may present with high intensity in the presence of oral microbiota changes. In addition, non-albicans species present number of virulence factors similar to that of C. albicans, with high pathogenicity. This study allows a better analysis of candidiasis prevention strategies aiming to promote improvement in the health and quality of life for the elderly.